2003
DOI: 10.1007/s00421-002-0716-z
|View full text |Cite
|
Sign up to set email alerts
|

Exhausting stretch-shortening cycle (SSC) exercise causes greater impairment in SSC performance than in pure concentric performance

Abstract: The purpose of the present study was to investigate the fatigue effect of repeated exhaustive stretch-shortening cycle (SSC) exercise on concentric muscle function. Ten healthy male subjects performed SSC exercise [92 (30) jumps] on a special sledge apparatus. Exhaustion occurred on average within 3 min. A squat jump (SJ) test utilizing a concentric-only action was performed immediately before and after the SSC exercise, and then 10 min, 20 min, 2 days and 4 days later. In addition, a drop jump (DJ) test using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
0
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 28 publications
8
69
0
11
Order By: Relevance
“…Similar findings have been reported for fatigue studies that used a submaximal SSC intensity workout. Avela and Komi (4), Gollhoffer et al (20,19), and Horita et al (25) reported a reduction in CT postfatigue. Avela and Komi (4), Hortia et al (26,27), and Nicol and Komi (33) indicated that because of submaximal SSC fatigue, the muscle mechanics and joint and muscle stiffness control are hampered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar findings have been reported for fatigue studies that used a submaximal SSC intensity workout. Avela and Komi (4), Gollhoffer et al (20,19), and Horita et al (25) reported a reduction in CT postfatigue. Avela and Komi (4), Hortia et al (26,27), and Nicol and Komi (33) indicated that because of submaximal SSC fatigue, the muscle mechanics and joint and muscle stiffness control are hampered.…”
Section: Discussionmentioning
confidence: 99%
“…Horita et al (27) reported an early recovery 2 hours postfatigue, but no potentiation effect was reported for the DJ. Horita et al (25) again examined the effect of a repeated exhaustive submaximal SSC fatigue protocol on DJs that were performed 20 minutes and 2 and 4 days after the workout. No potentiation effect was reported by the authors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entretanto, nossos resultados demonstram que durante um protocolo mais próximo da situação real de jogo, as alterações no comportamento neuromuscular, representadas pelas variáveis EMG, não foram significantes do início ao fim do protocolo. A divergência entre respostas neuromusculares pode estar relacionada com o menor efeito nos componentes contráteis e elásticos que potencializam o desempenho quando o protocolo é intermitente, como já citado na literatura (HORITA et al, 2002). Nessa perspectiva, a maioria dos estudos consideram somente as perspectivas neuromusculares e bioenergéticas ao avaliar a causa e o processo de instalação de fadiga na ação do salto vertical, induzidos pelos efeitos de protocolos contínuos e exaustivos (Bosco et al, 1986;Horita et al, 1996;Strojnik;Komi, 2000;Rodacki;Fowler;Bennett, 2002;McCaulley et al, 2007), diferentes da situação real de jogo.…”
Section: Discussionunclassified